Effect of reinceforcement on physical learning on motivation learning - Eka Madya Eka; Yunyun Yudiana; Komarudin (Gladi : Jurnal Ilmu Keolahragaan, 2022)
In this study, the author aims to determine the effect of reinforcement on physical learning on student motivation at SMPN 5 Cirebon. The method used by this researcher is a causal comparative with an ex post facto design. The population in this study were all students of SMPN 5 Cirebon with a sampling technique, namely Cluster Random Sampling with a total sample of 64 people consisting of class VIII 1 students and class VIII 2 students. The instrument used to collect data was using a questionnaire. motivation to learn. The questionnaire was used to measure the effect of reinforcement on learning motivation. The results of the data description can be seen that the effect of reinforcement on student motivation in class VIII 1 has an average value of 68.22 with a standard deviation of 8.315, the lowest value is 56 and the highest value is 100. In class VIII 2 the effect of reinforcement on student learning motivation has an average The average is 68.59 with a standard deviation of 6.997, the lowest value is 52 and the highest value is 80. The results of data processing show the value of sig. greater than 0.05 or 0.506, it can be concluded that the use of reinforcement in physical education learning can increase students' learning motivation.